Can Price Controls Be Optimal? The Economics of the Energy Shock in Germany - Tom Krebs; Isabella Weber (Institute of Labor Economics (IZA), 2024)
In the wake of the global energy crisis, many European countries used energy price controls to fight inflation and to stabilize the economy. Despite its wide adoption, many economists remained skeptical. In this paper, we argue that price controls should be part of the policy toolbox to respond to shocks to systemically important sectors because not using them can have large economic and political costs. We put forward our arguments in two steps. In a first step, we analyze the impact on the German economy and society of the global energy crisis that followed Russia's attack on Ukraine in February 2022. Our analysis shows that energy shocks matter. Specifically, the one-year GDP loss of the energy crisis 2022 amounts to 4 percent and is comparable to the short-run output losses during the COVID-19 crisis 2020 and the global financial crisis 2008. In addition, during the energy crisis 2022 inflation rates rose dramatically and real wages dropped more than in any other year in post-war Germany. There are also clear signs that the crisis is causing severe long-term economic damage (hysteresis effects). At the beginning of 2024, GDP is 7 percent and real wages are 10 percent below the pre-COVID-19 trend. We argue that the German government handled the immediate response to the energy shock well, but subsequently waited too long to introduce an energy price brake in 2022. This failure to act decisively in response to heightened economic insecurity coincided with a strong rise of the approval rates of the far-right AfD in the summer of 2022. We also show that the German energy price brake was an effective price stabilization policy for households, but did not protect the industrial base appropriately making it more likely that the German economy will continue to stagnate. In a final step, we turn to the use of price controls as an optimal policy response to an energy shock within a general equilibrium framework. We develop a simple production model with an energy sector and shows that price controls are socially optimal whenever self-fulfilling expectations generate endogenous price uncertainty in the wake of an energy shock. We also link our analysis to the so-called sunspot literature that was developed in the 1980s as a response to the rational-expectations revolution in macroeconomics. Finally, we use our theoretical analysis to shed some light on the economic policy debate and the resistance of German mainstream economists to the introduction of energy price controls in 2022.
Keywords: D52; D84; E12; E32; E64; Q43; Q48; 330; global energy crisis; German economy; endogenous uncertainty; price controls; inflation; stabilization policy